WORKSHOP DESAIN GRAFIS BERBASIS CANVA SEBAGAI UPAYA PENINGKATAN LITERASI DIGITAL DAN KREATIVITAS MASYARAKAT - Staimas, Abdul Rasyid Alawy; Muhamad Deden Apriliano; Eka Kharisma Putri; Dennis Atsilatu Zalfa; Gladys Lhexya Faradhila; Marenda Adhi Septiya (EL-KHIDMAH: Jurnal Diseminasi Pengabdian Kepada Masyarakat, 2025)
A graphic design workshop using the Canva application in TanjungsariVillage, Karangrejo District, Tulungagung Regency was held as an effort to 2 improve digital literacy and creative skills of the community. The background ofthis activity began with the low utilization of digital design technology in creatingpromotional media, so that many business actors still rely on manual methods orthird-party services. The graphic design workshop using the Canva application inTanjungsari Village, Karangrejo District, Tulungagung Regency aims to improvecommunity skills in creating digital promotional media. Activities include anintroduction to the basics of graphic design, training on the use of Canvafeatures, and practical design creation. As a result, participants were able toproduce attractive designs that are ready to be used for village activities.